2015
DOI: 10.1155/2015/346341
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Risk Factors Associated withClostridium difficileDiarrhea in Hospitalized Adult Patients

Abstract: Background. The epidemiology of Clostridium difficile infection has changed over time. Therefore, it is essential to monitor the characteristics of patients at risk of infection and factors associated with poor prognosis. Objective. To evaluate factors associated with C. difficile infection and with poor prognosis in those with documented C. difficile colitis. Methods. A retrospective case-control study of 75 patients with documented C. difficile colitis and 75 controls with hospital-acquired diarrhea of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
2
10
0
1
Order By: Relevance
“…Most previous work has identified the Charlson Comorbidity Index as an independent predictor of mortality; however, similar to our findings, other studies have not identified the Charlson Comorbidity Index as an independent predictor of mortality or poor outcomes [9, 42, 44]. The performance of aggregate comorbidity scores in predicting mortality is largely dependent on the underlying characteristics of the population under study [45, 46].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Most previous work has identified the Charlson Comorbidity Index as an independent predictor of mortality; however, similar to our findings, other studies have not identified the Charlson Comorbidity Index as an independent predictor of mortality or poor outcomes [9, 42, 44]. The performance of aggregate comorbidity scores in predicting mortality is largely dependent on the underlying characteristics of the population under study [45, 46].…”
Section: Discussionsupporting
confidence: 78%
“…The diagnosis codes for cognitive dysfunction include delirium, dementia, and amnestic and other cognitive disorders [32]. To our knowledge, nutrition deficiency has not been previously identified as an independent predictor; however, conditions that may cause or be related to various nutrition deficiencies have been identified as independent predictors of mortality, such as enteral tube feeding and inflammatory bowel disease [38, 42, 43]. Although enteral tube feeding and inflammatory bowel disease are not included in the codes for nutrition deficiency, nutrition deficiency codes capture a broad spectrum of nutritional conditions, such as unspecified protein-calorie malnutrition, other malnutrition, cachexia, and vitamin deficiencies [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were not able to assess the resolution in CDI symptoms, so composite endpoints did not include treatment failure (continued diarrhea) which is another common poor outcome of CDI. [40] As a consensus definition for CDI-attributable mortality is not established, we measured all-cause mortality. It is possible that some of the deaths we observed were attributable, at least in part, to diseases other than CDI.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] Long-term enteral tube feeding with elemental diets is one of the common but relatively unrecognized risk factors for the development of Clostridium difficile colitis. [ 31 ] Contamination and batch-to-batch inconsistency are more likely with homemade or blenderized feeds than with scientific feeds. Maintaining the microbial quality of hospital-prepared blenderized feeds within the published standards of safety is difficult.…”
Section: G Rading C Riteriamentioning
confidence: 99%